2023
DOI: 10.1186/s12879-023-07994-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuing the use of renin–angiotensin system inhibitors on mortality in patients hospitalized for coronavirus disease 2019: a systematic review, meta-analysis, and meta-regression analysis

Abstract: Background The effect of angiotensin-converting enzyme inhibitors (ACEIs)/angiotensin receptor blockers (ARBs) on mortality was preliminarily explored through the comparison of ACEIs/ARBs with non-ACEIs/ARBs in patients with coronavirus disease 2019 (COVID-19). Reaching a conclusion on whether previous ACEI/ARB treatment should be continued in view of the different ACE2 levels in the comparison groups was not unimpeachable. Therefore, this study aimed to further elucidate the effect of ACEI/ARB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
0
5
0
4
Order By: Relevance
“…Heart congestive failure and atrial fibrillation can be an adverse evolution in hypertensive patients, but actually, in the COVID era, hypertensive patients cannot be associated ACEI/ARAII use [ 56 , 57 ]. Recent studies have found that pre-treatment with ACEI/ARAII could be continued, as it was associated with lower hospital mortality, ICU admission and IMV in patients with COVID-19 [ 58 ]. For this reason, this medication should not be discontinued, especially ARAIIs [ 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heart congestive failure and atrial fibrillation can be an adverse evolution in hypertensive patients, but actually, in the COVID era, hypertensive patients cannot be associated ACEI/ARAII use [ 56 , 57 ]. Recent studies have found that pre-treatment with ACEI/ARAII could be continued, as it was associated with lower hospital mortality, ICU admission and IMV in patients with COVID-19 [ 58 ]. For this reason, this medication should not be discontinued, especially ARAIIs [ 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although regular treatment with ACE inhibitors appears to be a factor associated with the development of HF, in this case, it may be acting as a confounding factor because it is a common treatment for patients with previous HF, nephropathy, or hypertension, which are risk factors for HF. This fact observed with the ACE inhibitors can also be transferred to other treatments commonly used in HF and cardiovascular disease, such as statins or anticoagulant drugs [21]. Casas Rojo et al showed a protective role of ACEI/ARA2 and statins [14].…”
Section: Discussionmentioning
confidence: 99%
“…A AT2 tem uma grande expressão na vida uterina fetal reduzindo sua função decorrer da idade do paciente, e se comparado um adulto apresenta uma relação de 1,9 receptores de AT1 em relação a AT2, já o AT1 ao se ligar a Angiotensina II estimula a produção de vasopressina, aumenta o tônus simpático liberando catecolaminas, em especial a noradrenalina (Liu, et al, 2023). Já nas glândulas suprarrenais, a estimulação de catecolaminas também é expressada, aumentando a liberação de adrenalina que acabam causando uma vasoconstrição nos vasos sanguíneos de indivíduos com HAS crônica (Tanzadehpanah, et al,2023).…”
Section: Autor Título Objetivounclassified